1989
DOI: 10.1136/adc.64.12.1672
|View full text |Cite
|
Sign up to set email alerts
|

Diet and faecal flora in the newborn: breast milk and infant formula.

Abstract: SUMMARY This study examined the faecal flora on days 4, 14, and 28 of 17 breast fed babies and 26 bottle fed babies receiving a modern infant formula based on demineralised whey. Generally among breast fed babies bifidobacteria and staphylococci were the predominant organisms, whereas in the formula fed babies the predominant organisms were enterococci, coliforms, and clostridia. Despite the extensive modification of cows' milk to make an infant formula resemble human breast milk, the results are very similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
121
1
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(138 citation statements)
references
References 10 publications
7
121
1
4
Order By: Relevance
“…Con icting results have also been obtained regarding other groups of bacteria such as Bacteroides, clostridia, enterococci, lactobacilli and enterobacteria in breast-fed and formula-fed infants. Culture-based studies have shown a more diverse microbiota in formula-fed infants in comparison to those breast-fed (6,10). M oreover, in some studies formula-fed infants were found to have more complex faecal short-chain fatty acid (SCF A) pro les than breast-fed infants, which indicates a more complex microbiota in the aforementioned group (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Con icting results have also been obtained regarding other groups of bacteria such as Bacteroides, clostridia, enterococci, lactobacilli and enterobacteria in breast-fed and formula-fed infants. Culture-based studies have shown a more diverse microbiota in formula-fed infants in comparison to those breast-fed (6,10). M oreover, in some studies formula-fed infants were found to have more complex faecal short-chain fatty acid (SCF A) pro les than breast-fed infants, which indicates a more complex microbiota in the aforementioned group (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, in vivo the ingestion of lactoferrin has only a marginal influence on the intestinal microflora [1 1]. Moreover, it was shown that different effects on the microbial growth can be obtained by applying certain dietary formulations of milk proteins [11].…”
Section: Introductionmentioning
confidence: 99%
“…26 Anne sütü ile beslenen bebeklerin dışkı pH değeri, mama ile beslenenlere göre daha düşüktür. [27][28][29][30] Bullen ve ark.nın yaptığı çalışmada; anne sütü ile beslenen bebeklerin ilk üç ay boyunca dışkı pH değeri 5,1-5,4 iken, mama ile beslenenlerin dışkı pH değeri, ilk iki haftada 5,9-7,3, iki-beşinci haftalarda 7,0-8,2, beşinci haftalardan sonra ise 6,4 olmuştur. 31 On sekiz bebekle yapılan bir çalışmada, sekiz hafta boyunca sadece anne sütü ile beslenen bebeklerin dışkı pH değeri 5-6, anne sütü ile beraber ek besin alanların pH değeri 5-6 ile başlayıp, 6-8 arasına yükseldiği görülmüştür.…”
Section: Dişki Ph'siunclassified